1991
DOI: 10.1177/082585979100700102
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Control during the Last Week of Life on a Palliative Care Unit

Abstract: A recent report suggested that more than 50 % of terminal cancer patients have physical suffering that requires sedation in the last days of life. To evaluate this finding on our 14-bed palliative care unit, a retrospective analysis of 100 consecutive patients admitted for 6 days or more was carried out. Information was collected on major symptoms requiring treatment, symptom control at admission and during each of the last 7 days of life, medications used, and changes that may have contributed to sedation. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
192
3
7

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(206 citation statements)
references
References 19 publications
4
192
3
7
Order By: Relevance
“…The comparison of our results with published reports on opioid need is made even more difficult by the fact that, in the published papers, the investigated treatment period ranged from 24 h to several weeks [3,4,17]. There are only three retrospective studies analyzing opioid doses administered in the patients' last week of life [10,11,23]. In their retrospective study, Fainsinger et al [10] demonstrated a significant increase of the mean daily opioid dose from 493 to 659 mg parenteral morphine equivalent.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The comparison of our results with published reports on opioid need is made even more difficult by the fact that, in the published papers, the investigated treatment period ranged from 24 h to several weeks [3,4,17]. There are only three retrospective studies analyzing opioid doses administered in the patients' last week of life [10,11,23]. In their retrospective study, Fainsinger et al [10] demonstrated a significant increase of the mean daily opioid dose from 493 to 659 mg parenteral morphine equivalent.…”
Section: Discussionmentioning
confidence: 72%
“…There are only three retrospective studies analyzing opioid doses administered in the patients' last week of life [10,11,23]. In their retrospective study, Fainsinger et al [10] demonstrated a significant increase of the mean daily opioid dose from 493 to 659 mg parenteral morphine equivalent. In 31% of their patients, individual opioid dose increased during the last week of life.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a retrospective review by our group [27] we reported agitated delirium in 10% of patients as the most frequent problem requiring sedation in the last week of life. In a later study [30], we noted that the severity of agitated delirium requiring sedation in our palliative care unit had decreased to 3%.…”
Section: A Different Perspectivementioning
confidence: 99%
“…Thirty percent of patients with a terminal illness vomit, and 60% have nausea. These symptoms are demoralizing, demeaning and reduce patients' quality of life [1][2][3][4][5][6]. Nausea contributes to cachexia of advanced cancer, and vomiting exacerbates any pain experienced by patients with metastatic disease.…”
Section: Introductionmentioning
confidence: 99%